Kurikulum Nasional yang Berbasis Kompetensi Perguruan Tinggi dengan Mengacu pada Kerangka Kualifikasi Nasional Indonesia (KKNI) Untuk Menghasilkan Kualitas Manusia yang Kompeten - Christin Septina Basani (Faculty of Law, Maranatha Christian University, 2015)
Human resource needs, especially in the economy is the main source to sustain a nation. Human resources are created in a competent workforce and quality into its own competitiveness. Indonesian nation will enter the ASEAN Economic Community (AEC) will need to create a competent human resources. College as one of the graduates are ready to use in the workplace. One key factor is the quality of college graduates through the curriculum. Competency-based national curriculum with reference to national qualifications frameworks Indonesia will generate human resources in Indonesia are competent and competitive.